Martensitic stainless steel for high pressure hydrogen environment
The development of a martensitic stainless steel with a specific chemical composition addresses the challenge of achieving high tensile strength and ductility in high-pressure hydrogen environments, making it suitable for critical components in hydrogen fuelled engines.
Patent Information
- Application Number
- JP2025008107
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-28
AI Technical Summary
Existing stainless steels with martensite structures face challenges in achieving high tensile strength and ductility in high-pressure hydrogen environments, which is critical for components like sliding members in hydrogen fuelled internal combustion engines.
A martensitic stainless steel with a specific chemical composition optimized for high strength and hydrogen embrittlement resistance, including 0.18-0.40% C, 0.1-1.5% Si, 0.35-1.5% Mn, 0.04% or less P, 0.01% or less S, 0.20% or less Ni, 12.5-14.6% Cr, 1.0-3.0% (Mo+1/2W), 3.0% or less Cu, 0.3% or less Nb, and 0.10% or less N, which achieves a tensile strength of 1500 MPa or more and excellent ductility.
The optimized martensitic stainless steel exhibits high tensile strength and ductility even in high-pressure hydrogen environments, making it suitable for components that require high wear resistance and fatigue strength, such as sliding members in hydrogen fuelled engines.
Smart Images

Figure 2025068628000001 
Figure 2025068628000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a martensitic stainless steel for use in a high-pressure hydrogen environment. [Background technology]
[0002] Conventionally, SUS316L, an austenitic stainless steel with low susceptibility to hydrogen embrittlement, has been used for components used in high-pressure hydrogen environments (e.g., various sliding components in hydrogen production equipment, hydrogen transportation and storage equipment, hydrogen utilization equipment, infrastructure facilities, and hydrogen-fueled internal combustion engines). However, hydrogen is also being pressurized further in order to efficiently utilize gaseous hydrogen, which has a lower energy density than liquid hydrogen, and it is expected that SUS316L, which has a tensile strength of about 600 MPa, will not have enough strength. For this reason, various steels have been proposed with the aim of increasing strength without reducing hydrogen embrittlement resistance.
[0003] For example, in Patent Document 1, the alloy contains, by mass%, C: 0.10% or less, Si: 1.0% or less, Mn: 3% or more and less than 7%, Cr: 15 to 30%, Ni: 10% or more and less than 17%, Al: 0.10% or less, N: 0.10 to 0.50%, and at least one of V: 0.01 to 1.0% and Nb: 0.01 to 0.50%, with the balance being Fe and impurities, in which P is 0.050% or less and S is 0.050% or less, the alloy has a tensile strength of 800 MPa or more, a grain size number (ASTM E 112) of 8 or more, and has an alloy carbonitride with a maximum diameter of 50 to 1000 nm at a concentration of 0.4 particles / μm when observed in cross section. 2 Austenitic stainless steel for high pressure hydrogen gas, characterized by the above-mentioned contents, has been proposed. This proposal is excellent in that it achieves both hydrogen embrittlement resistance and high strength without adding more alloy than necessary.
[0004] Patent Document 2 proposes a high-strength steel that contains, by mass%, 0.20-0.50% C, 0.01-0.40% Si, 0.10-1.0% Mn, 0.02% or less P, 0.02% or less S, 1.0-5.0% Ni, 0.5-2.5% Cr, 0.1-1.5% Mo, 0.005-0.3% V, and optionally one or two of 0.1% or less Nb and 0.5% or less Cu, with the balance being Fe and unavoidable impurities, and that has a composition such that Ceq (Ceq=C+Mn / 6+Si / 24+Ni / 40+Cr / 5+Mo / 4+V / 14) represented by the following formula is 0.75 or more, thereby having high strength and excellent hydrogen embrittlement properties in a high-pressure hydrogen environment. This proposal is excellent in that it achieves both high strength and hydrogen embrittlement resistance by using martensite or bainite structures, which are easier to obtain higher strength than austenite structures but are highly susceptible to hydrogen embrittlement.
[0005] Furthermore, Patent Document 3 proposes a high-pressure hydrogen container having a chemical composition containing, by mass%, C: 0.20 to 0.50%, Si: 0.05 to 0.50%, Mn: 0.05 to 1.00%, P: 0.025% or less, S: 0.0200% or less, Al: 0.005 to less than 0.050%, Cr: 0.30 to 1.50%, Mo: 0.15 to 1.50%, Ti: 0.002 to 0.050%, B: 0.0001 to 0.0050%, N: less than 0.0070%, and O: less than 0.0050%, with the balance being Fe and impurities, containing 0.010 to 0.050 mass% solid solution C, having a tensile strength of 900 to 1100 MPa, and a yield ratio of 85% or more. This proposal is superior in that it achieves high strength of 1000 MPa or more in addition to hydrogen embrittlement resistance while using the same martensite or bainite structure as Patent Document 2. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5131794 [Patent Document 2] JP 2014-227573 A [Patent Document 3] JP 2019-183218 A Summary of the Invention [Problem to be solved by the invention]
[0007] Members used in the above-mentioned high-pressure hydrogen environment are required to ensure high strength and ductility even in the hydrogen environment. In addition, sliding members such as parts for internal combustion engines that use hydrogen as fuel (bearings, valves) and sealing parts for hydrogen gas boosting compressors tend to have a short life due to friction and wear with other members, and further high strength and ductility are required. Patent Document 1 is an effective method for increasing the strength while maintaining the excellent hydrogen embrittlement resistance of austenitic stainless steel, but it has not been examined whether the stainless steel has the strength characteristics required for use as a sliding member, and there is a risk of shortening the life of the parts due to insufficient strength. Patent Documents 2 and 3 are also effective methods for increasing the hydrogen embrittlement resistance of steel products having a martensite or bainite structure, but like Patent Document 1, there is a possibility that the strength will be insufficient when used as a sliding member in a hydrogen environment. Therefore, an object of the present invention is to provide a stainless steel having excellent ductility while having high tensile strength even in a high-pressure hydrogen environment by improving the hydrogen embrittlement resistance of steel having a martensite structure. [Means for solving the problem]
[0008] The inventors investigated the problem of susceptibility to hydrogen embrittlement, which is a major issue with stainless steels having a martensitic structure, and discovered that by optimizing the chemical composition of stainless steel, it is possible to increase resistance to hydrogen embrittlement and obtain high strength even in a high-pressure hydrogen environment, thereby arriving at the present invention.
[0009] That is, the present invention has a composition, in mass%, of C: 0.18 to 0.40%, Si: 0.1 to 1.5%, Mn: 0.35 to 1.5%, P: 0.04% or less, S: 0.01% or less, Ni: 0.20% or less, Cr: 12.5 to 14.6%, one or two of Mo and W according to the relational formula (Mo+1 / 2W): 1.0 to 3.0%, Cu: 3.0% or less, Nb: 0.3% or less, N: 0.10% or less, the balance being Fe and unavoidable impurities, When a hollow specimen was subjected to a slow strain rate tensile test in high pressure hydrogen, the tensile strength was 1500 MPa or more and was greater than the fracture stress; this martensitic stainless steel is suitable for use in high pressure hydrogen environments. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a stainless steel that has high tensile strength even in a high-pressure hydrogen environment and also has excellent ductility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As described above, an important feature of the present invention is that a martensitic stainless steel that exhibits excellent high strength properties and good ductility even in a high pressure hydrogen environment of 1 MPa or more (preferably 5 MPa or more) has been found. The reasons for the composition limitations of the present invention will be explained below.
[0012] C: 0.18 to 0.40 mass% (hereinafter simply referred to as "%") C is an element effective in increasing the hardness of the martensite structure after quenching and tempering. However, if there is too much C, the C forms carbides, which reduces the amount of Cr and Mo dissolved in the matrix, deteriorating the corrosion resistance of the product, and the amount of C dissolved in the matrix increases, deteriorating the hydrogen embrittlement resistance of the product. On the other hand, if there is too little C, there is less C that dissolves in the matrix and exerts a solid solution strengthening effect, so the hardness and strength decrease. Therefore, the C content is set to 0.18 to 0.40%, preferably 0.20% or more, and more preferably 0.30% or less.
[0013] Silicon: 0.1 to 1.5% Silicon is used as a deoxidizing agent during the melting process, and is an element that can be unavoidably contained. If there is too much silicon, the hardness of the annealed material (i.e., the stainless steel of the present invention before quenching and tempering (before adjustment to the product hardness)) increases, and the cold workability decreases. Therefore, the Si content is set to 0.1 to 1.5%, preferably 1.0% or less, more preferably 0.8% or less, further preferably 0.5% or less, and preferably 0.2% or more.
[0014] Mn: 0.35~1.5% Mn is used as a deoxidizer during the melting process and is an element that may be unavoidably included. In addition, when solid-phase nitrogen absorption treatment is performed for the purpose of improving strength, Mn is an element that has the effect of promoting the solid solution of nitrogen into the structure. However, if there is too much Mn, the austenite structure is stabilized, making it difficult to obtain a martensite structure and high surface hardness. Therefore, the Mn content is set to 0.35 to 1.5%, preferably 0.5% or more, and more preferably 1.0% or less.
[0015] ·P:0.04% or less P is an element that deteriorates the toughness of the product, so its content is set to 0.04% or less, preferably 0.03% or less.
[0016] ·S: 0.01% or less S is an element that forms MnS in the presence of Mn and improves the machinability of the product. However, if the content is too high, hot workability deteriorates, so the S content is set to 0.01% or less, preferably 0.005% or less, and more preferably 0.003% or less.
[0017] ·Ni: 0.20% or less Ni is an element effective in improving corrosion resistance against non-oxidizing acids such as formic acid, sulfuric acid, and hydrochloric acid. However, if there is too much Ni, the Cu phase in stainless steel becomes fine (the area ratio of the coarse Cu phase becomes small), and cold workability deteriorates. In addition, in stainless steel products after quenching and tempering, the austenite structure is stabilized, making it difficult to obtain a martensite structure and high surface hardness. In addition, when solid-phase nitrogen absorption treatment is performed, a large amount of N is dissolved in the surface layer, so only the surface layer becomes an austenite structure, and hardness is significantly reduced. Therefore, the Ni content is 0.20% or less. It is preferably 0.18% or less, and more preferably 0.15% or less.
[0018] Cr: 12.5~14.6% Cr is an element that forms an amorphous passive film on the surface of stainless steel, imparting corrosion resistance to the product. In addition, when solid-phase nitrogen absorption treatment is performed, it also has the effect of increasing the amount of nitrogen that can be dissolved in stainless steel. However, if there is too much Cr, the ferrite structure is stabilized, making it difficult to obtain a martensite structure and high surface hardness. Therefore, the Cr content is set to 12.5 to 14.6%, preferably 14.0% or less, and more preferably 13.5% or less.
[0019] One or both of Mo and W according to the formula (Mo+1 / 2W): 1.0 to 3.0% Mo and W are similar elements and can be treated equally in the relational formula (Mo+1 / 2W). Mo and W have the effect of stabilizing the passivation film of stainless steel in a solid solution state, and are elements that also contribute to improving the corrosion resistance of the product surface. In addition, when the passivation film of Cr is scratched, Mo and W have the effect of increasing the Cr content at the scratched location and strengthening the repair ability of the passivation film. Since these elements have the effect of increasing the amount of N absorbed during quenching, for example, by performing quenching treatment in a nitrogen atmosphere, a hardened layer of nitrogen is formed on the surface of stainless steel, and the strength and fatigue strength can be improved. However, if there are too many Mo and W, the ferrite structure is stabilized, as with the above-mentioned Cr, and it becomes difficult to obtain a martensite structure. Therefore, the content of Mo and W is 1.0 to 3.0% in the relational formula (Mo+1 / 2W). It is preferably 1.2% or more. It is also preferably 2.5% or less.
[0020] ·Cu:3.0% or less Cu is an essential element for simultaneously achieving high hardness and excellent corrosion resistance according to the present invention. In particular, Cu is an effective element for improving corrosion resistance against non-oxidizing acids such as formic acid, sulfuric acid, and hydrochloric acid. However, if the Cu content is too high, the hot workability is extremely deteriorated. Therefore, the Cu content is set to 3.0% or less, and preferably 2.5% or less.
[0021] ·Nb: 0.3% or less Nb has the effect of suppressing the growth of prior austenite grain boundaries and refining the martensite structure. Refining the crystal grains contributes to improving strength and ductility, and has the effect of reducing susceptibility to hydrogen embrittlement. However, if there is too much Nb, C and N form Nb compounds, which reduces the solid solubility of C and N and reduces the effect of improving hardness. Therefore, Nb can be contained in an amount of 0.3% or less as necessary. It is preferably 0.2% or less.
[0022] ·N: 0.10% or less N is an element that dissolves in martensite or precipitates as a compound in stainless steel products after quenching and tempering, improving strength, ductility, and hydrogen embrittlement resistance. The reason for the above-mentioned effect of N is not clear, but when N is added, the carbides generated by tempering become carbonitrides, which are finely dispersed, making it possible to achieve both strength and ductility, and it is thought that the finely dispersed carbonitrides trap hydrogen, suppressing hydrogen localization and improving hydrogen embrittlement resistance. N is also an element that can suppress the precipitation of delta ferrite, which is harmful to the microstructure, in stainless steel before quenching and tempering. However, if there is too much N, bubbles will be generated during casting, significantly worsening manufacturability, and it can also be a factor in the crystallization of coarse nitrides after solidification. Furthermore, when the material before quenching is finished into the product shape, it is prone to work hardening during cold working, and it is necessary to process it while repeating intermediate annealing, and machinability will also deteriorate. Therefore, the N content is set to 0.10% or less. It is preferably 0.08% or less, and more preferably 0.06% or less. In addition to the elements described above, the elements contain Fe and unavoidable impurities.
[0023] Next, the test method and its characteristics specified in the present invention will be described. In the present invention, a slow strain rate tensile test using a hollow test piece (hollow test piece low strain rate tensile test in high pressure hydrogen) is used as a tensile test in a high pressure hydrogen environment. The main high pressure hydrogen environment test methods are a method in which a tensile test is performed using a solid tensile test piece in a chamber capable of applying high pressure and a predetermined hydrogen pressure is applied, and a method in which a tensile test piece is hollowed out and high pressure hydrogen gas is applied therein to perform a tensile test. Both methods are the same in that they can evaluate hydrogen embrittlement behavior in a high pressure hydrogen environment, so in the present invention, the characteristics are evaluated by a hollow test piece high pressure hollow test, which is a simpler method among high pressure hydrogen environment tests. In addition, hydrogen embrittlement depends on the strain rate during the tensile test, and the hydrogen sensitivity increases as the strain rate decreases, so in the present invention, a tensile test is performed at a low strain rate to clarify the presence or absence of hydrogen resistance.
[0024] The stainless steel of the present invention has a tensile strength of 1500 MPa or more obtained by the above-mentioned hollow test piece low strain rate tensile test in high pressure hydrogen. In general, the higher the strength of a metal material, the higher the hydrogen sensitivity, so materials exceeding 1000 MPa are prone to hydrogen embrittlement and have a large decrease in strength in a hydrogen environment. Sliding members used in a hydrogen environment are required to have high wear resistance and fatigue strength, and high strength correlated with these properties is used as an index of evaluation. Therefore, in the present invention, the tensile strength is specified to be 1500 MPa or more in order to achieve excellent sliding properties. And the martensitic stainless steel of the present invention has a tensile strength greater than the breaking stress, and does not break in the plastic region from the elastic region until the tensile strength is reached. Generally, martensitic stainless steels exceeding 1000 MPa or more often break in the elastic region or immediately after reaching the plastic region from the elastic region, resulting in an unstable fracture mode with small elongation and reduction in size. The martensitic stainless steel of the present invention exhibits a behavior in which, in a tensile test, it undergoes localized contraction and breaks after passing from the elastic region to the plastic region and then reaching the tensile strength indicating the maximum stress (in other words, the tensile strength is greater than the breaking stress). This indicates that the martensitic stainless steel of the present invention has both high strength and excellent ductility in a hydrogen environment. In addition, when it is desired to emphasize high strength properties, it is preferable to carry out solid-phase nitrogen absorption treatment on the martensitic stainless steel of the present invention. This solid-phase nitrogen absorption treatment can be carried out by setting the atmosphere during quenching to a nitrogen atmosphere when carrying out quenching and tempering treatment on the martensitic stainless steel having the alloy composition of the present invention. It is preferable to set the quenching temperature at 1000 to 1100°C, since this allows sufficient nitrogen to be dissolved in solid solution. In addition, after the quenching process and before carrying out the tempering process, sub-zero treatment at -50°C or less can also be carried out. On the other hand, when it is desired to further increase the hydrogen embrittlement resistance effect, it is also possible to omit the solid-phase nitrogen absorption treatment.
[0025] The martensitic stainless steel of the present invention has a high tensile strength of 1500 MPa or more even in a high-pressure hydrogen environment, and is also excellent in ductility, making it suitable for use in members in a high-pressure hydrogen environment. In particular, it is preferable to use it in applications requiring high strength and corrosion resistance, such as various sliding members and high-strength products in hydrogen production equipment, hydrogen transportation and storage equipment, hydrogen utilization equipment or infrastructure facilities, and hydrogen-fueled internal combustion engines. EXAMPLES
[0026] 10 kg of molten metal melted in a high-frequency induction melting furnace was cast to produce stainless steel ingots No. 1 to No. 3 having a plurality of component compositions shown in Table 1. Next, these ingots were subjected to heat treatment at a holding temperature of 1080 to 1150°C for 60 minutes. This holding temperature was set as the forging start temperature, and hot forging was performed with a forging ratio (cross-sectional area before forging / cross-sectional area after forging) of about 10, followed by cooling. After cooling, annealing was performed at a holding temperature of 780 to 860°C for 4 hours or more, and a stainless steel material with a thickness of about 15 to 20 mm was obtained.
[0027] [Table 1]
[0028] For the materials No.1 to No.3, a hollow test piece was subjected to a low strain rate tensile test in high pressure hydrogen. The materials No.1 and No.2 of the present invention were held at 1090°C for 30 minutes as a quenching treatment, then cooled, subjected to deep cooling at -77°C, held at 365°C for 2 hours as a tempering treatment, and then air-cooled. The material No.3 of the comparative example was held at 1050°C for 30 minutes as a quenching treatment, then cooled, subjected to deep cooling at -77°C, held at 150°C for 3 hours as a tempering treatment, and then air-cooled. These materials were processed into hollow tensile test pieces with a parallel part diameter of 4 mm, a parallel part length of 20 mm, a total length of 70 to 90 mm, and an internal through hole diameter of 1 mm. Hydrogen was then introduced into these test pieces so that the pressure in the internal through hole was 10 MPa at room temperature, and the strain rate was 5.0 x 10 -5Tensile tests were conducted at 1000 rpm / s. The test results are shown in Table 2. From Table 2, No. 1 and No. 2 of the present invention did not break in the plastic region from the elastic region until the tensile strength was reached, and showed a high tensile strength of 1500 MPa or more. The breaking stress was lower than the tensile strength, and the elongation was about 10%, and the reduction in area was 20% or more, showing ductile fracture behavior. On the other hand, the comparative example showed a high tensile strength of 1690 MPa, but the breaking stress was the same as the tensile strength, and there was almost no elongation or reduction in area, resulting in brittle fracture. This shows that the stainless steel of the present invention shows high strength and ductility, as well as hydrogen embrittlement resistance, even under high pressure environments.
[0029] [Table 2]
Claims
[Claim 1] The composition is, in mass%, C: 0.18 to 0.40%, Si: 0.1 to 1.5%, Mn: 0.35 to 1.5%, P: 0.04% or less, S: 0.01% or less, Ni: 0.20% or less, Cr: 12.5 to 14.6%, one or two of Mo and W according to the relational formula (Mo+1 / 2W): 1.0 to 3.0%, Cu: 3.0% or less, Nb: 0.3% or less, N: 0.10% or less, the balance being Fe and unavoidable impurities; A martensitic stainless steel for use in high-pressure hydrogen environments, which has a tensile strength of 1,500 MPa or more and a value greater than the fracture stress when a hollow test piece is subjected to a slow strain rate tensile test in high-pressure hydrogen.
Citation Information
Patent Citations
Uretanhorimaano butsuritekiseishitsuno kairyoho
JP1976031794A
High strength steel having excellent high-pressure hydrogen environment embrittlement resistance properties and production method therefor
JP2014227573A
High pressure hydrogen container, and steel material for high pressure hydrogen
JP2019183218A